Can you hear/see me? Multisensory integration of signals does not always facilitate mate choice. (23rd June 2022) - Coss, Derek A; Ryan, Michael J; Page, Rachel A; Hunter, Kimberly L; Taylor, Ryan C
Abstract: Females of many species choose mates using multiple sensory modalities. Multimodal noise may arise, however, in dense aggregations of animals communicating via multiple sensory modalities. Some evidence suggests multimodal signals may not always improve receiver decision-making performance. When sensory systems process input from multimodal signal sources, multimodal noise may arise and potentially complicate decision-making due to the demands on cognitive integration tasks. We tested female túngara frog, Physalaemus ( =Engystomops ) pustulosus, responses to male mating signals in noise from multiple sensory modalities (acoustic and visual). Noise treatments were partitioned into three categories: acoustic, visual, and multimodal. We used natural calls from conspecifics and heterospecifics for acoustic noise. Robotic frogs were employed as either visual signal components (synchronous vocal sac inflation with call) or visual noise (asynchronous vocal sac inflation with call). Females expressed a preference for the typically more attractive call in the presence of unimodal noise. However, during multimodal signal and noise treatments (robofrogs employed with background noise), females failed to express a preference for the typically attractive call in the presence of conspecific chorus noise. We found that social context and temporal synchrony of multimodal signaling components are important for multimodal communication. Our results demonstrate that multimodal signals have the potential to increase the complexity of the sensory scene and reduce the efficacy of female decision making. Abstract : Animal courtship signals are complex. Males of many species advertise their availability as a mate using a complex suite of acoustic, visual, olfactory, or other signals. In túngara frogs, females assess potential mates using both acoustic and visual signals of courting males. In some conditions, the visual cue of a male's inflatable vocal sac can improve the ability of a female to discriminate among different male advertisement calls. When the mating scene becomes noisy, however, a female's ability to choose among the advertisement calls may be compromised. Here we demonstrate how visual and acoustic noise can interfere with female mate choice decisions.